An Increase Performance Of Unbalanced Induction Motor At High Temperature - Ahmad Rizal Nurika; Beni Satria; Zulkarnain Lubis (Sean Institute, 2024)
With the increase in temperature that causes the life of the induction motor to decrease and often occurs in induction motors is the unbalanced phase voltage which causes the performance of the induction motor to decrease. in this paper describes the effect of unbalanced voltage on the temperature of a three phase induction motor, which is expected to be used as a reference for isolation and protection of the induction motor itself. The induction motor in an unbalanced voltage state has a higher temperature increase than the state of the five-phase induction motor in a balanced voltage, which is 0.36 0C / m for balanced voltage, 0.72 0C / m for 1% unbalanced voltage and 0.84 0C / m for 3% unbalanced voltage based on infrared thermometer measurements. While measurements using resistance measurements are 0.64 0C/m for balanced voltage, 0.934 0C/m for 1% unbalanced voltage and 1.147 0C/m for 3% unbalanced voltage.